Pathogenesis, evaluation, and recent management of diabetic foot ulcer - Wijaya, Lorettha; Budiyanto, Arief; Astuti, Indwiani; Mustofa, . (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Diabetic foot ulcers (DFUs) are a major health problem as the number of patients continues to increase, are difficult to heal, require enormous management costs, and deteriorate the quality of life of patients, their families and societies. The pathogenesis of DFUs is complex. Most important factors that increase the risk of DFUs are peripheral neuropathy, foot deformities, frequent minor trauma, and peripheral arterial disease. Neuropeptides derangement, hypoxia, hyperglycemia, and infection act as the cause of chronicity of DFUs. Therefore, during the initial evaluation of DFU, patients need to be checked for their metabolic status, presence or absence of peripheral neuropathy, vascular insufficiency, foot deformities, and infection of the ulcer and its underlying bone. Then, DFUs are classified by the severity of vascular insufficiency, the depth of the wound, and the severity of the infection. This classification system helps clinicians to determine whether the patient needs to be hospitalized or amputated and helps to establish DFU management strategies. In the management of DFUs, adequate blood flow to the wound area should be achieved. Glycemic control and standard wound care should be encouraged. Standard wound care includes debridement, offloading, wound moisture balance with suitable dressing, edema control, and infection control. Education about preventive foot care should be taught to the patients and their families. As the pathogenesis and management of DFUs are complex, a multidisciplinary team consists of expert individuals in their respective fields should be involved.